Erga Omnes Dalam Putusan Mahkamah Konstitusi Menyelesaikan Perselisihan Hasil Pemilukada (Studi Terhadap Putusan MK Nomor 135/PHP.BUP-XIX/2021) - Edelweisia Cristiana; Ni Wayan Eka Sumartini (IAHN Tampung Penyang Palangka Raya, 2022)
The purpose of this paper was to examine the principle of erga omnes in the decision of the Constitutional Court which annulled the results of the Sabu Raijua Regency General Election due to the violation of the requirements for regional head candidates, namely the issue of citizenship. The author has discussed several provisions related to erga omnes in the decision of the Constitutional Court, using the normative juridical method. Through the statutory approach (statute approach), literature study, and case approach (case approach). The type of analysis that has been applied is descriptive interpretive. The results of this paper have included regulations regarding the General Election Commission, the Election of Governors, Regents, and Mayors, the Citizenship of the Republic of Indonesia, the Constitutional Court, and the Judicial Power. Tujuan penulisan untuk menelaah prinsip erga omnes dalam putusan Mahkamah Konstitusi yang membatalkan hasil Pemilukada kabupaten Sabu Raijua akibat pelanggaran syarat calon kepala daerah, yakni masalah kewarganegaraan. Penulis membahas beberapa ketentuan terkait erga omnes dalam putusan Mahkamah Konstitusi, dengan menggunakan metode yuridis normatif. Melalui pendekatan perundang- undangan (statue approach), studi literatur, dan pendekatan kasus (case approach). Jenis analisis yang diterapkan adalah deskriptif interpretatif. Hasil dari tulisan ini meliputi peraturan mengenai Komisi Pemilihan Umum, Pemilihan Gubernur, Bupati, dan Walikota, Kewarganegaraan Republik Indonesia, Mahkamah Konstitusi, dan Kekuasaan Kehakiman.